(untitled) (Journal of the Bangladesh Agricultural University, 2026)
This study investigates the effect of incorporating three strand twisted nylon rope fibers into concrete to improve its mechanical behavior, particularly compressive and splitting tensile strength. Concrete mixes were prepared with fiber dosages of 0, 2, 5, and 10 kg/m³ using a 1:2:4 mix proportion and tested at curing ages of 7, 14, and 28 days. Standard cylindrical specimens (100 × 200 mm) were cast, cured in water, and tested for compressive and tensile strengths. The diameter of nylon fiber is 1.95 mm and length are 25-50 mm. The results showed that moderate fiber inclusion improved tensile strength but excessive addition reduced both strength and workability. The fiber dosages investigated were 2, 5, and 10 kg/m³ (kg of fiber per cubic meter of concrete). Among these, 2 kg/m³ represents the low or optimal dosage, while 5 and 10 kg/m³ represent higher dosages. The optimum performance was observed at 2 kg/m³ which achieved approximately 30.66% higher tensile strength and 16.47% higher compressive strength at 7 days compared to the plain concrete. At 28 days, 2 kg/m³ maintained 9.27% higher tensile strength and 1.20% higher compressive strength, while higher fiber contents (5-10 kg/m³) led to significant reductions of up to 50% in both strengths. Excessive fiber content reduces workability and bonding efficiency, leading to strength loss. Therefore, a fiber dosage of around 2 kg/m³ is recommended for practical use in non-structural and medium-strength concrete applications such as pavement layers, floor slabs, sidewalks, precast panels and repair works, where improved crack control and toughness are desired. J Bangladesh Agril Univ 24(2): 137–143, 2026